Development Of A Multi-Objective Model With Multiple Allocation Of Limited Capacity In Terms Of Uncertainty For Location Axes - Irani, Hoonaz Shamayi; Jafari, Davood (The Turkish Online Journal of Design Art and Communication, 2016)
One of the topics of hub location is new facility location that has recently been the focus of many researchers. Hub location issues generally arise in the network transport and communications. Role of a transition point plays axial point where incoming traffic from this source together and sent to the other focal point or the traffic is divided into several arteries that are directed towards other purposes. Due to the uncertainty in the current situation is one of the most difficult and the most important responsibilities of project managers are considering the uncertainties in modeling. How to insert the uncertainty in the model and solving different issues impact on the performance and success of the project is the main goal of the current study. The current study is applied and exploratory research which introduces a Mathematical Model and analyzes it using Gomez Software.
Keywords: Location Hub; Location Facilities; Uncertainty; Multiple Allocation; robust Optimization